Concomitant neurodegenerative pathologies contribute to the transition from mild cognitive impairment to dementia. Issue 7 (4th March 2021) - McAleese, Kirsty E.; Colloby, Sean J.; Thomas, Alan J.; Al‐Sarraj, Safa; Ansorge, Olaf; Neal, James; Roncaroli, Federico; Love, Seth; Francis, Paul T.; Attems, Johannes
Abstract: Introduction: The aged brain frequently exhibits multiple pathologies, rather than a single hallmark pathology (pure pathology [PurP]), ranging from low/intermediate levels of additional pathology (LowP) to mixed severe pathology (mixed SevP). We investigated the frequency of PurP, LowP, and mixed SevP, and the impact of additional LowP on cognition. Methods: Data came from 670 cases from the Brains for Dementia research program. Cases were categorized into PurP, mixed SevP, or a main disease with additional LowP; 508 cases had a clinical dementia rating. Results: 69.9% of cases had LowP, 22.7% had PurP, and 7.5% had mixed SevP. Additional LowP increased the likelihood of having mild dementia versus mild cognitive impairment (MCI) by almost 20‐fold (odds ratio = 19.5). Discussion: Most aged individuals have multiple brain pathologies. The presence of one additional LowP can significantly worsen cognitive decline, increasing the risk of transitioning from MCI to dementia 20‐fold. Multimorbidity should be considered in dementia research and clinical studies.